Surveillance of foodborne disease outbreaks in China, 2003–2017. (December 2020) - Li, Weiwei; Pires, Sara M.; Liu, Zhitao; Ma, Xiaochen; Liang, Jinjun; Jiang, Yuyan; Chen, Jiang; Liang, Junhua; Wang, Santao; Wang, Liansen; Wang, Yafang; Meng, Can; et al.
Abstract: Foodborne disease remains a major public health problem worldwide. To understand the epidemiology and changes of foodborne disease in China, data reported to the National Foodborne Disease Outbreak Surveillance System during 2003–2017 were collected. A total of 19, 517 outbreaks, which resulted in 235, 754 illnesses, 107, 470 hospitalizations, and 1, 457 deaths, were reported in this period. Of the 13, 307 outbreaks with known etiology, 31.8% of outbreaks were caused by poisonous mushrooms, followed by Vibrio parahaemolyticus (11.3%), saponin (8.0%), Salmonella (6.8%), nitrite (6.4%), pesticide (4.8%), Staphylococcus aureus (4.2%) and Bacillus cereus (3.0%). Among 18, 955 outbreaks with reported setting, 46.6% were associated with food prepared in a household, followed by 22.5% with food prepared in a restaurant, and 18.4% prepared in a canteen. Of the 13, 305 outbreaks associated with a single food category, fungi (mainly poisonous mushroom) were the most commonly implicated food category, followed by meats, vegetables, aquatic animals, condiments, poisonous plants (such as saponin, tung oil or seed, aconite) and grains (such as rice, noodle, rice noodle). Analysis of foodborne disease outbreaks can provide insight into the most important causative agents and sources of foodborne disease, and assist public health agencies determine the high-risk etiology and food pairs, specific points of contamination and settings to reduce foodborne disease illnesses. Highlights: A total of 19, 517 outbreaks were collected during 2003–2017 in China. Poisonous mushroom was the most common cause of outbreaks. Household, restaurant and canteen were the most common settings in China. The major implicated foods were fungi, meat, vegetable, grain and aquatic products.